Laporan Kasus: Melanoma Maligna Intrakranial Primer - Andrea Valentino; Rijalun Arridho (Fakultas Kedokteran Universitas Riau, 2019)
Primary intracranial malignant melanoma is an extremely rare tumor. Most of the intracranial malignant melanoma are metastatic from skin. Diagnosis needs multidisciplinary workup to exclude metastatic melanoma. We are reporting a case of young girl with decrease consciousness and tetraplegia. CT scan revealed a solitary tumor mass in the brain. Histopathological examination and confirmed by immunohistochemistry showed that the type of tumor was intracranial primary malignant melanoma and by excluding metastatic melanoma. Tumor excision was performed in patient and adjuvant chemotherapy was given, but residual tumors were present multiple.